Characteristics of VNIISPK apple cultivars on semi-dwarf rootstock 54-118 - A. M. Galasheva; N. G. Krasova; Z. E. Ozherelieva (Овощи России, 2020)
Relevance. Due to the wide diversity of cultivars and rootstocks, the selection of more productive, commercial and adapted graft-rootstock combinations for industrial orchards in the Orel region and the entire Central Chernozem region is relevant.Materials and methods. The studies were carried out at the Russian Research Institute of Fruit Crop Breeding (VNIISPK) on the bases of the laboratory of cultivar study and cultivar agrotechnics of pome crops and the laboratory of physiology of fruit plant resistance. Winter apple cultivars of VNIISPK breeding ‘Sinap Orlovsky’, ‘Veteran’, ‘Orlik’, ‘Rozhdestvenskoye’, ‘Svezhest’, ‘Bolotovskoye’, ‘Veniaminovskoye’ and control cultivar ‘Antonovka Obyknovennaya’ on the vegetatively propagated semi-dwarf rootstock 54-118 were taken as objects of the studies. The orchard was planted in autumn 2013, the planting scheme was 6 mx3m.Results. The studied apple cultivars have good compatibility with 54-118 rootstock, provide good tree development and low-sized crown. The highest yield on average for three years was in scab-immune apple cultivars ‘Bolotovskoye’ (4.6 t/ha), ‘Rozhdestvenskoye’ (3.4 t/ha) and ‘Venyaminovskoye’ (3.2 t/ha). The highest indicators for the load of the crop on the crown volume, crown projection area, and cross-sectional area of the stem were for ‘Svezhest’ and ‘Bolotovskoye’. As a result of determining the frost resistance of apple cultivars in mid-January to temperatures up to -38...-40°C, it was revealed that in the hardened state, the cultivars showed frost resistance of buds and tissues of annual shoots with reversible damage at -38°C in the middle of winter. A decrease in temperature to -40°C in January increased damage to buds and wood in the studied varieties, while the bark was characterized by greater frost resistance. According to the degree of damage to the cortex in January, when the temperature dropped to -40°C, ‘Rozhdestvenskoye’, ‘Svezhest’, and ‘Sinap Orlovsky’ were at the control level.